Homicide and Love - Smith, Steven G. (Philosophy & theology, 1991)
For perspicuous comparison and evaluation of moral positions on life-and-death issues, it is necessary to take into account the different meanings that killing and getting killed can bear in the two dimensions of dealing with persons (intention meeting intention) and handling them. A homicidal scenario in Sir Gawain and the Green Knight shows the possibility of courteous dealing coinciding with lethal handling. The extreme possibility of lovingly affirming persons while killing them, suggested by the Augustinian “kindly severity” ideal for state-sponsored punitive killing, requires the killers’ affirmation of a fleshliness and fallibility shared with their victims; but love can accept killing only provisionally, since it postulates freedom from the constraints that are felt to require killing.